Portal vein thrombosis prevalence and associated mortality in cirrhosis in a nationally representative inpatient cohort. Issue 6 (4th November 2018) - Cool, Josephine; Rosenblatt, Russell; Kumar, Sonal; Lucero, Catherine; Fortune, Brett; Crawford, Carl; Jesudian, Arun
Abstract: Background and Aim: Portal vein thrombosis (PVT) is increasingly common in cirrhotics, but its impact on mortality and outcomes is unclear. Studies evaluating PVT have been limited by small sample size. This study analyzes the trend of the prevalence of PVT and its associated mortality in hospitalized decompensated cirrhotics. Methods: The Nationwide Inpatient Sample, the largest nationally representative database of hospital discharges, was queried from 1998 to 2014. Inpatients older than 18 years with decompensated cirrhosis were included, while those who received liver transplantation or had hepatocellular carcinoma were excluded. The primary outcomes were the trend in prevalence and associated mortality with PVT. Secondary outcomes included identifying risk factors of PVT and the effect of PVT on complications of portal hypertension. Multivariable logistic regression evaluated the outcomes. Results: A total of 3 045 098 discharges were included, of which 1.5% had PVT. PVT prevalence increased from 0.7% to 2.4%, annual percent change of 9%. Mortality associated with PVT declined from 11.9% to 9.1%, annual percent change of −3.0%. In multivariable analysis controlling for factors associated with mortality in cirrhotics, PVT was associated with an increased risk of mortality (OR 1.12, P < 0.001). Multivariable logistic regression also demonstrated that PVT significantly increased the risk of acute kidney injury (OR 1.75, P < 0.001) and hepatorenal syndrome (OR 1.62, P < 0.001). Conclusions: The prevalence of PVT is increasing while its associated mortality is decreasing. However, PVT still is associated with risk of mortality and kidney injury, implying a significant impact on cirrhotic outcomes.